2020
DOI: 10.56381/jsaem.v4i3.29
|View full text |Cite
|
Sign up to set email alerts
|

Spine and Whiplash Injuries Related to Passenger Car Crashes in Malaysia

Abstract: Spinal injury is one of the most devastating traumas that can be sustained in a motor vehicle crash. In passenger car crashes, the most common injuries related to the spine is whiplash injury or Whiplash Associated Disorder (WAD); however, the injury was relatively unknown in Malaysia. This study explored the possibility of elucidating whiplash injury locally by studying the insurance claims made by passenger car occupants involved in traffic crashes. The objectives of the study were to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…As for spinal cord injuries, traffic accidents were the leading cause in the United States at 48% [22][23][24][25]. An Italian study showed that falls accounted for 41% of spinal cord injuries, and traffic accidents accounted for 34% [26]. Patients with spinal cord injuries at the level C1-C3 had a 6.6-fold increased risk of mortality and 2.2-fold risk if they were injured at the C4-C5 level compared with patients with thoracic spinal cord injuries or lower [27].…”
Section: Truck Driversmentioning
confidence: 99%
“…As for spinal cord injuries, traffic accidents were the leading cause in the United States at 48% [22][23][24][25]. An Italian study showed that falls accounted for 41% of spinal cord injuries, and traffic accidents accounted for 34% [26]. Patients with spinal cord injuries at the level C1-C3 had a 6.6-fold increased risk of mortality and 2.2-fold risk if they were injured at the C4-C5 level compared with patients with thoracic spinal cord injuries or lower [27].…”
Section: Truck Driversmentioning
confidence: 99%